2010
DOI: 10.3178/hrl.4.75
|View full text |Cite
|
Sign up to set email alerts
|

A high measurement frequency based assessment of shallow groundwater fluctuations in Metouia Oasis, South Tunisia

Abstract: Abstract:The Metouia Oasis (South Tunisia) is increasingly being impacted by high soil salinity, leading to yield losses and ultimately to farmland abandon. In this area shallow groundwater rise is considered the major factor responsible for salt accumulation in soils. However, limited data exist on groundwater fluctuations in Metouia Oasis, despite the criticality of such information for accurate soil salinity assessment. In this study, groundwater behavior was monitored at a high measurement frequency. An ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Such quantification is not easy to handle due to the dynamic nature of these systems having a very fast response time to hydrologic change owing to their closeness to soil surface [1]. In fact, many researchers reported rapid and disproportionate water table rise in response to rainfall events observed in shallow groundwater systems [4][5][6]. They showed that shallow water tables can often rise disproportionately compared to the volume of infiltrated water.…”
Section: Introductionmentioning
confidence: 99%
“…Such quantification is not easy to handle due to the dynamic nature of these systems having a very fast response time to hydrologic change owing to their closeness to soil surface [1]. In fact, many researchers reported rapid and disproportionate water table rise in response to rainfall events observed in shallow groundwater systems [4][5][6]. They showed that shallow water tables can often rise disproportionately compared to the volume of infiltrated water.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows scatter plots created with data collected between 1 May and 16 October 2014 ( Figure 2) and displays the relationships between SWC, DWT, and streamflow in Otter Creek. SWC values in this figure were calculated as a weighted average of measurements taken at the four depths (5,10,20, and 50 cm) and are considered representative of conditions within the top 65 cm of the soil column. Panels in Figure 8 display a clear non-linear relationship between streamflow and either SWC or DWT and a close-to-linear relationship between DWT and SWC.…”
Section: Comparison Of Timing For Various Eventsmentioning
confidence: 99%
“…The authors in [18] demonstrated the importance of the groundwater component in flood generation using high-resolution water table monitoring in 10 wells and other hydrometric and geochemical data. Other studies have reported distributed patterns of pore water pressure head [19], soil salinity impacts on farmland [20], and dynamics of the hyporheic zone [21].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Cloke et al (), using the laboratory experiment of Abdul and Gillham () as a platform, showed numerically that the proportion of pre‐event discharge is determined by the length of the transitional stage of ridge development. Additionally, several studies treating the Harran Plain (Çullu et al ), the Metouia Oasis (Ibrahimi et al ), and the Songnen Plain (Chi and Wang ) found that frequent and rapid groundwater table fluctuations may not only cause more salt to accumulate on the surface but also enhance this phenomenon. Therefore, it is critical to thoroughly understand the processes responsible for the development of groundwater ridging in hillslope‐riparian zones.…”
Section: Introductionmentioning
confidence: 99%